Downeshelea litorale Santarém & Borkent & Spinelli & Felippe-Bauer 2018, sp. nov. - Santarém, Maria Clara Alves; Borkent, Art; Spinelli, Gustavo; Felippe-Bauer, Maria Luiza (Zenodo, 2018)
Downeshelea litorale sp. nov. (Figures 6a–h, 9c–d, 10) Downeshelea multilineata : Huerta et al. 1999: 494 (misidentification; Mexico record). Diagnosis Male. The only species of Downeshelea in the Americas with the following combination of features: gonostylus 0.58–0.68 length of gonocoxite; parameres fused for 0.23–0.30 of total length; stem nearly straight basally, expanded distally in inner portion; distal portion very elongate, strongly curved distally (Figure 9d); aedeagus rectangular, basal arch somewhat U-shaped, extending to 0.34–0.42 of total length (Figure 9c). Female. The only species of Downeshelea multilineata group in the Americas with medium-sized wing (1.05–1.25 mm) (Figure 6d); midtarsomere 1 with 4–5 ventral spines; hind tibia uniformly brown; two slightly unequal spermathecae (Figure 6h). Description Male. Head . Eyes slightly contiguous in lower area; antennal ratio 1.00–1.07 (1.02, n = 8); palpal ratio 2.20–2.75 (2.46,n = 8) (Figure 6b). Thorax. Brown, without definite pattern in slide-mounted specimens. Wing (Figure 6a) with greyish spot over CuA 1, CuA 2 extending into cua 1, anal cell, reaching wing margin in CuA 1; 2 nd radial cell twice longer than 1 st; wing length 1.00–1.17 (1.08, n = 8) mm; breadth 0.32–0.40 (0.37, n = 8) mm; costal ratio 0.71–0.75 (0.73, n = 8). Halter brown, distal portion of knob darker. Legs (Figure 6c) brown, hind femur darker subapically. Fore-, hind tarsomere 1 with one basal, one apical spine; midtarsomere 1 with two basal, two apical, 4–6 other ventral spines; apical spines of tarsomeres 2–4 of fore-, mid-, hind legs: 2–2–2, 2–2–1, 1–1–1; fore tarsal ratio 2.21–2.35 (2.27, n = 8), mid tarsal ratio 2.22– 2.55 (2.42, n = 8), hind tarsal ratio 2.09–2.33 (2.17, n = 8); claws 0.38–0.50 (0.44, n = 8) length of their respective tarsomere 5. Abdomen. Dark brown. Terminalia (Figure 9c): tergite 9 with quadrate apex, apicolateral process elongate, slender; sternite 9 slightly concave anteriorly, posterior margin with a moderately convex median lobe bearing 3–4 long setae. Gonocoxite nearly 2.15– 2.36 (2.27, n = 8) times longer than basal width; gonostylus with blunt tip, 0.58–0.68 (0.63, n = 8) length of gonocoxite. Parameres (Figure 9d) 1.06–1.23 (1.11, n = 8) times longer than aedeagus, fused for 0.23–0.30 (0.26, n = 8) of total length; knob heavily sclerotised, bulbous; stem nearly straight basally, expanded distally in inner portion; distal portion very elongate, strongly curved distally, 0.62–0.73 (0.69, n = 8) of total length. Aedeagus rectangular, slightly sclerotised laterally, basal arch somewhat U-shaped, deep, extending to 0.34–0.42 (0.38, n = 8) of total length, distal portion with moderately deep mesal excavation terminating in two short, pointed, serrate processes. Female. Similar to male with usual sexual differences; antennal ratio 1.06–1.17 (1.11, n = 5) (Figure 6e); palpus as in Figure 6g, palpal ratio 2.20–2.60 (2.36, n = 5); mandible with 11–12 teeth. Wing as in Figure 6d; wing length 1.05–1.25 (1.15, n = 5) mm; breadth 0.40–0.50 (0.46, n = 5) mm; costal ratio 0.75–0.80 (0.77, n = 5). Fore-, hind tarsomere 1 with one basal and one apical spine; midtarsomere 1 with two basal, two apical, 4–5 other ventral spines; apical spines of tarsomeres 2–4 of fore-, mid-, hind legs: 1–1–1, 2–2–1, 1–1–2; fore tarsal ratio 2.25–2.50 (2.32, n = 5), mid tarsal ratio 2.45–2.54 (2.49, n = 5), hind tarsal ratio 2.37–2.50 (2.43, n = 5); fore, mid- leg claws 0.66–0.87 (0.71, n = 5) length of their respective tarsomeres 5; hind leg claw about 1.0–1.4 (1.11, n = 4) as long as tarsomere 5 (Figure 6f). Abdomen with genital sclerite nearly triangular, trilobed, tapering anteriorly. Two slightly unequal spermathecae (Figure 6h), measuring 55–65 (60, n = 5) by 43–50 (47, n = 5) µm and 50–58 (54, n = 4) by 40–48 (44, n = 4) µm. Third rudimentary spermatheca nearly 7.5 µm. Specimens examined Holotype male adult, labeled ‘ Holotype Downeshelea litorale Santarém, Borkent, Spinelli and Felippe-Bauer’, ‘ Downeshelea multilineata (Lutz), BAHAMAS, W.I. Coral Harbour, New Province, 23 November 1968, G.M. Stobes col., light trap’ (USNM); allotype female adult, labeled ‘ Allotype Downeshelea litorale Santarém, Borkent, Spinelli and Felippe-Bauer’ same data as holotype (USNM). Paratypes labeled as follows: 1 male, ‘ BRAZIL, Rio de Janeiro, Jacarepaguá, Tanque, July 1972, Tavares and Souza cols.’ (CCER); 1 male, ‘ COSTA RICA, Limón, Parque Nacional Cahuita, Sector Puerto Vargas, 5m, 9 August–15 October 2002, E. Rojas. Malaise’ (CNCI); 1 male, same data except 15 December 2002 – 15 January 2003 (MNCR); 1 male, ‘ Downeshelea multilineata (Lutz), DOMINICA, Cabrit Swamp, 23 February 1965, W. Wirth, Bredin-Archbold, Smithsonian biological survey Dominica’ (USNM); 2 males, 3 females, ‘ Downeshelea multilineata (Lutz), JAMAICA, Westmoreland Parish Negril, Crystal Waters Tropical Hammock, 20 November 1968, R. E. Woodruff, black light trap’ (1 male, 1 female CCER; 1 male, 2 females USNM); 1 male, 1 female, same data except ‘ 22 June 1970, light trap, E.G. Farnworth’ (USNM); 3 males, 2 females, ‘ Downeshelea multilineata (Lutz), GRAND CAYMAN, 14 July 1991, P. Fitzgerald, black light trap’ (1 male, 1 female CCER; 2 males, 1 female USNM); 1 female, same data except October 1991 (USNM); 2 males, ‘ MEXICO, Yucatan, Reserva Río Lagartos, Tizimin, entrada a Zacbo, selva baja, 19 March 1996, light trap, Ibáñez-Bernal col.’ (CAIM). Distribution and bionomics This species is known from the Mexico, Bahamas, Grand Cayman, Jamaica, Dominica, Costa Rica (Limón) and Brazil (Rio de Janeiro) (Figure 10). It has been found in forests near coastal areas. Etymology The name of this species reflects its distribution along seashores in the Caribbean, Mexico, Costa Rica and Brazil (Latin – litorale = seashore). : Published as part of Santarém, Maria Clara Alves, Borkent, Art, Spinelli, Gustavo & Felippe-Bauer, Maria Luiza, 2018, New Neotropical species of Downeshelea Wirth and Grogan and redescription of D. multilineata (Lutz) (Diptera: Ceratopogonidae), pp. 509-540 in Journal of Natural History (J. Nat. Hist.) (J. Nat. Hist.) 52 (9 - 10) on pages 533-535, DOI: 10.1080/00222933.2018.1437231, http://zenodo.org/record/5178489 : {"references": ["Huerta H, Ibanez-Bernal S, Felippe-Bauer ML. 1999. New records of biting midges (Diptera: Ceratopogonidae) in Mexico. Entomol y Vectores. 6: 491 - 499."]}